Phylogenetic analysis and docking study of neuraminidase gene of influenza A/H1N1 viruses circulating in Iran from 2010 to 2019 - Sina Moeini; Atefeh Mohebbi; Behrokh Farahmand; Parvaneh Mehrbod; Fatemeh Fotouhi (Virus Research, 2023)
Influenza A viruses (H1N1) have been consistently one of the most evolving viruses that escape from vaccine-induced immunity. Although there has been a rapid rise in human influenza virus knowledge since the 2009 pandemic, the molecular information about Iranian strains is still inadequate. The aim of this study was to analyze the neuraminidase (NA) segment of the Iranian isolates in terms of phylogenetic, antiviral resistance, and vaccine efficiency. Ninety-three NA sequences collected among 1758 nasopharyngeal swab samples during the 2015–2016 influenza season were sequenced and submitted to NCBI. Moreover, all the submitted Iranian influenza H1N1 NA sequences since 2010 till 2019 were included in the study.Software including MEGA-X, MODELLER, UCSF ChimeraX, Auto-Dock 4.2, and other online tools were used to analyze the phylogenetic relationship, vaccine efficiency, and binding affinity to sialic acid of the selected NA proteins. Moreover, the information about antiviral drug resistance mutations of NA were gathered and compared to the Iranian NA segments to check the presence of antiviral drug-resistant strains.The phylogenetic study showed that most Iranian NA sequences (between 2015 and 2016) were located in a single clade and following years were located in its subclade by 3 major mutations (G77R/K, V81A, and J188T). Resistant mutations in drug targets of NA including I117M, D151E, I223V, and S247N were ascertained in 10 isolates during the 2015–2016 flu seasons.Investigation of vaccination effect revealed that Iranian isolates in 2017 and 2018 were best matched to A/Brisbane/02/2018 (H1N1), and in 2019 to A/Guangdong-Maonan/SWL1536/2019 (H1N1).Furthermore, we performed an in-silico analysis of NA enzymatic activity of all Iranian sequences by assessment of enzyme stability, ligand affinity, and active site availability. Overall, the enzyme activity of four Iranian strains (AUG84119, AUG84157, AUG84095, and AUG84100) was assumed as the maximum enzyme activity. This study highlighted the evolutionary trend of influenza A virus/H1N1 circulating in Iran, which provides a preliminary viewpoint for a better comprehension of new emerging strains’ virulence and thus, more appropriate monitoring of influenza virus A/H1N1 during each outbreak season.